Perbedaan Kualitas Terjemahan antara Mahasiswa dan Penerjemahan Mesin Daring - Herdiany, Ghalda Yuli (Jurnal Penerjemahan, 2021)
Translation has, today, become a vital activity that cannot be separated from students in their learning process and also in other aspects of life. In translating, students often rely on Machine Translation (MT) as it is time and energy efficient. However, people have come to doubt the translation quality of MT. Meanwhile, the accuracy of information could only be achieved when translation results fulfill certain criteria. Therefore, this study aims to reveal the differences in translation quality from English to Indonesian produced by students and MT. To this end, the research applies the qualitative comparative analysis to obtain the different translation results of students and MT. This study is conducted at a public university in Serang–Banten, with the participation of 5 students. Data obtained from the translation of students and MTs are then analyzed by applying Nababan’s theory (2012). The analysis succinctly reveals that students obtain higher average scores than MT in three aspects, namely accuracy, acceptability, and readability. In the fourth aspect, the analysis uncovers that both students and MT actually produce similar errors, namely in word choice and sentence structure. Finally, this study suggests that MT should be used to complement students' translation. Keywords: translation, translation quality, Machine Translation, Google Translate, and Bing Microsoft Translator.